THE ROLE OF OVERSIGHT IN REDUCING THE PHENOMENON OF FINANCIAL AND ADMINISTRATIVE CORRUPTION IN GOVERNMENT INSTITUTIONS (AN ANALYTICAL STUDY OF A SAMPLE OF AUDITORS AND ACCOUNTANTS IN BANKS AFFILIATED TO AL-RIFAI DISTRICT) - Radwan Jabbar Gouda (Scholar Express Journals, 2023)
The aim of the research is to identify the role of the internal auditor in reducing the phenomenon of administrative and financial corruption in Iraqi government institutions, specifically in the surveyed banks of the Rifai district, and to identify the research problem that lies in the weakness of the role of the internal auditor. The research and the diagnosis of the impact relationship on the dependent variable, based on sources, scientific references, university theses and previous studies as a secondary source. The questionnaire was also used as a basic means to achieve the goal of the research as a primary source. As for the second axis, it relates to the phenomenon of administrative and financial corruption in public government institutions, and the third axis relates to the role of the internal auditor to reduce the phenomenon of administrative and financial corruption in public government institutions. For the analysis, the statistical package for social sciences (SPSS) program was relied upon To several conclusions, the most important of which.
Keywords: internal auditor; administrative and financial corruption